2021
DOI: 10.1016/j.ajem.2021.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department bounceback characteristics for patients diagnosed with COVID-19

Abstract: Background The global healthcare burden of COVID-19 continues to rise. There is currently limited information regarding the disease progression and the need for hospitalizations in patients who present to the Emergency Department (ED) with minimal or no symptoms. Objectives This study identifies bounceback rates and timeframes for patients who return to the ED due to COVID-19 after initial discharge on the date of testing. Methods Using the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(10 reference statements)
1
3
1
Order By: Relevance
“…Our findings also support previous research suggesting a high rate of return of COVID-19 patients to the ED. The 16.5% return visit and 9.6% admission rate in our cohort are in line with previous reports from singlehospital systems [14]. Kilaru et al (2020) reported lower return (8.6%) and admission (4.7%) rates, but their study only assessed patients up to 72 hours and, unlike our approach, could not capture patients who went outside their hospital system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings also support previous research suggesting a high rate of return of COVID-19 patients to the ED. The 16.5% return visit and 9.6% admission rate in our cohort are in line with previous reports from singlehospital systems [14]. Kilaru et al (2020) reported lower return (8.6%) and admission (4.7%) rates, but their study only assessed patients up to 72 hours and, unlike our approach, could not capture patients who went outside their hospital system.…”
Section: Discussionsupporting
confidence: 90%
“…Kilaru et al (2020) reported lower return (8.6%) and admission (4.7%) rates, but their study only assessed patients up to 72 hours and, unlike our approach, could not capture patients who went outside their hospital system. Similarly, Haag et al (2021) reported only a 9% return rate up to 30 days, although this study enrolled patients not only from EDs but also assessed a mix of urgent care and drivethrough-testing facilities. Beiser et al (2021) recently published a multicenter, ED-based study involving 116 hospitals and found a 21% return visit rate at 30 days, with 7.6% of patients admitted, although these figures were not restricted to COVID-19-related repeat visits or admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have examined the risk of adverse events after diagnosis of COVID‐19, these have generally focused on serious short‐term adverse events such as intubation or death in a predominantly admitted cohort 25 or readmissions after hospital discharge 26,27 . The overall rate of 30‐day ED return after discharge index visit discharge in our study was 21.4% (1610/7529), which is significantly higher than the 14.6% rate reported in a smaller study of patients who were symptomatic and discharged from a mix of EDs, immediate care centers, and drive‐through testing facilities within a single health system 28 . This difference is likely reflective an overall lower patient acuity within that mixed‐site study.…”
Section: Discussioncontrasting
confidence: 57%
“… 26 , 27 The overall rate of 30‐day ED return after discharge index visit discharge in our study was 21.4% (1610/7529), which is significantly higher than the 14.6% rate reported in a smaller study of patients who were symptomatic and discharged from a mix of EDs, immediate care centers, and drive‐through testing facilities within a single health system. 28 This difference is likely reflective an overall lower patient acuity within that mixed‐site study. Our overall hospital readmission rate at 30 days of 7.6% (571/7529) is surprisingly high compared with the rate of 8.5% reported in a population of patients discharged from the ED or inpatient care with COVID‐19 pneumonia on supplemental oxygen.…”
Section: Discussionmentioning
confidence: 91%
“…However, in line with our findings, they reported hypertension as the second most common comorbidity. Another study conducted on patients with COVID-19 showed that most patients who returned to the ER had pulmonary, cardiac, or infectious symptoms [ 12 ].…”
Section: Discussionmentioning
confidence: 99%